Vegetable as Rabbit Feed: between Benefits and Health Risks: Sayuran sebagai Pakan Kelinci: antara Manfaat dan Risiko terhadap Kesehatan - Nasihin, Ahmad (Buletin Peternakan Tropis, 2025)
This review aims to explore the benefits and risks of using vegetables as rabbit feed. The study was conducted using a literature review method, examining various scientific sources including journal articles, e-books, and other relevant literature related to the selected topic. Based on the findings of the review, vegetables can serve as a supplementary feed due to their rich content of nutrients such as amino acids, vitamins, minerals, and antioxidants that support rabbit health. Several types of vegetables such as water spinach, carrot leaves, carrots, and sweet potato leaves have been shown to improve feed intake and rabbit growth when given in appropriate proportions. Feeding vegetables can provide dietary variety, offer additional fiber, and serve as a cost-effective feed alternative. However, excessive vegetable intake poses several health risks, including digestive disturbances, diarrhea, bloating, impaired nutrient absorption, and potential toxicity due to the presence of anti-nutritional factors such as tannins, oxalates, phytates, and other compounds. In addition, pesticide contamination and residues may negatively affect rabbit health. Therefore, proper feeding strategies are necessary, such as ensuring vegetables are free from contaminants, wilting them before feeding, and regulating the quantity to avoid replacing primary fiber sources like grass or hay. A recommended inclusion rate of vegetables is 8–10% of the total daily diet. With proper feed management, vegetables can be a valuable alternative to support rabbit growth and health without causing adverse effects. This review provides insight into the potential benefits and risks of vegetable use as rabbit feed, along with appropriate recommendations to help achieve optimal daily nutritional balance